Relation of the chondromalatia patellae to proximal tibial anatomical parameters, assessed with MRI - Tabary, Mohammadreza; Esfahani, Azadehsadat; Nouraie, Mehdi; Babaei, Mohammad Reza; Khoshdel, Ali Reza; Araghi, Farnaz; Shahrezaee, Mostafa (Radiology and oncology, 2020)
Background Magnetic resonance imaging (MRI) is a non-invasive highly sensitive tool for diagnosing chondromalacia patellae in the early stages. Many studies have evaluated patellar and trochlear morphology with different radiologic indices. We aimed to assess the discriminative power of tibial, patellar, and femoral indices in MRI for chondromalacia patellae. Patients and methods 100 cases of chondromalacia, as well as 100 age-matched controls among the patients who underwent knee MRI between February 2017 and March 2019, were included. The standard protocol of knee MRI was applied and the diagnosis of chondromalacia was made on MRI findings. Chondromalacia subjects were also classified as grade 1 to 4 according to the Modified Outerbridge's MRI grading system. We measured 25 MRI parameters in the knee and adjacent structures to determine the relation between chondromalacia patellae and anatomical MRI parameters. Results Tibial slope, trochlear depth, lateral trochlear inclination, and lateral patellar tilt angle had significant correlation with chondromalacia. Any increase in lateral trochlear inclination and lateral patellar tilt angle could increase the probability of the disease (Odds ratio [OR] 1.15, 1.13; 95% CI: 1.03-1.30; 1.02-1.26, respectively), while any increase in medial tibial slope and trochlear depth could decrease the probability of chondromalacia (OR 0.85, 0.06; 95% CI: 0.73-0.98, 0.02-0.17, respectively). We also designed a model for the severity of disease by using the patellar height index (relative odds ratio: 75.9). Conclusions The result of this study showed the novelty role of tibial anatomy in developing chondromalacia and its mechanism. We also concluded that patellar height might be an important factor in defining disease severity.